Iowa Ornithologists' Union, Quarterly field report, winter 1976-1977 - Halmi, Nicholas S.et al; Iowa Ornithologists' Unionet al (1976)
Quarterly field report for winter 1976-1977 titled "Field reports". It is published in Iowa Bird Life March 1977. The report is an annotated draft. Supporting documentation includes a Nicholas S. Halmi letter to Vernon M. Kleen regarding an update on sightings from Gladys Black, March 7, 1977. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1976-1977. Epson - sheet feed/flatbed